Social protest at mining territories: Examining contentious politics at mining districts in Chile. (September 2022) - Irarrazaval, Felipe
Abstract: The territorial turn in the research agenda about extractive industries and development has remarked the uneven and entangled processes through which industries anchor across space. Whereas the uneven developmental performance of mining areas has been largely discussed, this turn offers fertile ground to interact with the literature about contentious politics and examine how the spatial distinction of mining territories also shapes local unrest and social mobilization. This paper examines social protest dynamics at mining districts by exploring four dimensions of contentious politics and comparing its prevalence between mining and non-mining districts. For such a purpose, the paper distinguishes between mining and non-mining districts through a cluster analysis based on a set of mining-related variables. Afterward, it analyses four relevant dimensions of social protests related to extractive industries (labor, public services, local politics, and environmental) based on a database of protest actions registered between 2009 and 2019 in 18 newspapers. The results show that mining districts are distinguished by social protests related to public services and labor demands, while social protest related to local politics and environmental issues does not exhibit a significant difference between mining and non-mining districts. Thereby, the districts in which mining exerts a larger influence face higher rates of social protest only regarding labor and public services. Highlights: Research about social conflicts and extractive industries has overlooked the manifold sources of social protest at mining territories. The districts in which mining exert a larger influence distinguish from non-mining districts mainly because of protest-related labor demands. Social protest demanding better public services, such as education or healthcare, is also relevant in the districts in mining districts. Conversely, rates of protests related to environmental and local government demands do distinguish between mining and non-mining districts. It is necessary to examine deeply the sources of unrest in the spaces in which mining anchors and shape local development.